Padr\~oes de especializaç\~ao comercial no Mercosul - Daniel Grimaldi; Flávio Carneiro; Luís Felipe Oliveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper analyses the competitiveness evolution in Argentina, Brazil, Paraguay and Uruguay within Mercosur trade flows, on the relative specialization perspective and changes in the distribution of revealed comparative advantage among distinct product categories. For this purpose, it measures the Balassa revealed comparative advantage indexes, of each country between 1991 and 2008, based on UNComtrade data. Then, goods were grouped in categories according to Lall (2000), and two methodologies were applied: one using markovian transition matrixes and other based in non-parametric estimates of the probability density functions of the IB. The analysis suggests a relative reduction, throughout the period, on the number of goods in which Brazil had revealed comparative advantage, which may mean that Brazil lost market within Mercosur in a significant number of products, or that Brazil has undergone a process of trade specialization. Another conclusion is that, even after the Mercosur, member countries failed to increase the participation on trade within partners, a result that would not be expected from the creation of a free trade area.
Keywords: F15; 330; Internationale Arbeitsteilung; Komparativer Vorteil; Argentinien; Brasilien; Paraguay; Uruguay; Mercosur-Staaten